Walking as an intervention : Apprehensions of the railway in Bauru-SP - Souza, Lucas do Nascimento; Fiorin, Evandro; Rodrigues, Laís da Silva (National Journal of City Management, 2021)
How to analyze urban areas in the contemporary modern city upon the plurality of forms of appropriation of public spaces? This paper seeks to contribute to qualitative studies on urban perception through the method of cartography. Thus, this writing does not deal with the search for information or data collection, but with the immersion in the ongoing process present in the territory of the old railway bed in the city of Bauru-SP. The text highlights a research practice little explored in this spatial cutout, which tends to contribute to the impact on urban perception and future interventions in this area, as the decanted sociospatial layers are revolved and an urban imaginary little explored is accessed through the development as a research modality.